Integrating person directed care into the client experience - Tammy Marshall; Joann Reinhardt; Orah Burack; Audrey Weiner (The Beryl Institute, 2017)
Culture Change leaders in long term care have identified creative ways to implement a model of Person Directed Care to improve the client experience by providing choice, instilling dignity, and fostering deep relationships among its community members. One organization created an environment of care called "The Small House" and educated its' workforce using the Green House® Project Legacy Alignment program to redesign the organizational structure, experience and environment. Interviews were conducted with elders, staff, and family members (N=20) about their experiences living, working or visiting a Small House as compared to experiences in their previous dwelling, a traditional nursing home. They were asked to describe the biggest difference between the Small House and the traditional nursing home model, and the differences in the two models in terms of the food, personal care, and relationships. Study participants were also asked to rate on a likert scale satisfaction with their experiences in the traditional nursing home and the Small House. Results showed that satisfaction ratings were higher among all groups living, working, or visiting the Small House compared to the traditional nursing home setting. The themes that emerged most often in comparing the Small House homes to the traditional nursing home included choice, homelike atmosphere, positive sensory environment, and evidence of close relationships in the Small House. The Small House homes studied in this qualitative investigation appear to have captured the important elements that create real home and consistent care partners who know the elders deeply to keep them comfortable and engaged.